Análisis jurisprudencial de la economía del bienestar en la constitución económica material peruana - Ahomed Chávez, Omar Abraham (2020)
This work researches the welfare economics in the Peruvian material economic constitution through the precedents of the Constitutional Court of Peru. It has as objective to identify the principles and theories that the Constitutional Court uses to resolve conflicts between economic groups. The research will differentiate between material economic constitution and formal economic constitution within of the Peruvian social market economy.